Inflammatory cytokines and specific factors influencing lung cancer progression - Millat, Md. Shalahuddin; Hasan, Md. Mahmudul; Uddin, Mohammad Sarowar; Salam, Md. Abdus; Aziz, Md. Abdul; Akhter, Irin; Hussain, Md. Saddam; Mohammad, Nor; Tanjum, Farjana Afrin; Mostaq, Md. Saqline; Mahmud, Md. Ashiq; Amin, Mohammad Nurul; et al. (Cancer pathogenesis and therapy, 2025)
Lung cancer (LC) is one of the main causes of illness and death. Inflammation is a facilitator of cancer growth and progression, affecting processes such as angiogenesis, antiapoptotic pathways, and DNA adduct formation. Cytokines are small proteins that can accelerate or slow tumor growth by controlling associated signaling processes such as cell proliferation, development, metastasis, and apoptosis. This review reveals the role of tumor necrosis factor-alpha, interferon-gamma, transforming growth factor-beta (TGF-β), and interleukins in LC. Macrophages play a role in non-small cell lung cancer (NSCLC) pathogenesis and are associated with poor prognosis. A nested case–control study revealed that elevated concentrations of IL-6 and IL-8 were strongly associated with the risk of LC. Specifically, the odds ratio for IL-6 and IL-8 in former smokers (fourth quartile vs. first quartile) were 2.70 (95% confidence interval [CI]: 1.55–4.70) and 2.83 (95% CI: 1.18–6.75). Because C-reactive protein levels are elevated in patients with NSCLC with larger and higher-grade tumors, CRP has been identified as a systemic indicator of chronic inflammation. Insulin-like growth factors influence cellular signal transduction pathways and contribute to tumorigenesis. Soluble tumor necrosis factor receptors have been explored for their role in NSCLC prognosis, highlighting their association with chromogranin. Transient receptor potential cation channel, subfamily M, member 7 (TRPM7), urokinase plasminogen activator, matrix metalloproteinases, and monocyte chemoattractant protein-1 have been identified with a focus on their expression patterns and prognostic significance in LC tissues. Moreover, lung angiogenesis induces vascular endothelial growth factor, soluble intercellular adhesion molecule-1, myeloperoxidase, and tissue inhibitors of metalloproteinase expressions. In conclusion, this review thoroughly summarized the inflammatory cytokines and specific factors influencing LC, providing the basis for further research on potential treatment approaches. [Display omitted] •Inflammation is the body's normal response to injury or infection.•Cytokines like tumor necrosis factor-alpha (TNF-α), interferon-gamma (IFN-γ), and interleukin (IL) regulate inflammation and immune function.•Chronic inflammation increases the risk of lung cancer (LC) and promotes tumor growth.•Targeting cytokines such as IL-6 and TNF-α may offer better therapies for LC.•Immune modulation through cytokine inhibition could reduce tumor-associated inflammation and enhance treatment efficacy.